Housewife Empowerment Training Skills through Processing Waste Products to be Economic Value - Gayatri, Askardiya Mirza; Hapsari, Sri; Aqil, Deden Ibnu (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2017)
The purpose of this research is to improve the skills of housewives Sawangan, Depok, in the use of waste cloth into brooches, necklaces, earrings, towels, and other accessories through community empowerment. Empowerment is a community effort to increase the capacity to prepare themselves for the provision of knowledge and skills. Stages empowerment counseling begins with awareness of the importance of taking wastewater to protect the environment and entrepreneurship motivation, followed by waste processing training, mentoring makes products to become independent, as well as promotional strategies. Through counseling and training, is expected to explore the potential that there is in the group of mothers in the household so that it can generate income to the household economy, either as principal or as an additional revenue, as well as a provision for opening an independent business in the creative industries. If it is implemented properly and sustained, will indirectly assist in economic growth in both the domestic and regional levels in the District Sawangan.